The Microbiome of Catfish (Ictalurus punctatus) Treated with Natural Preservatives During Refrigerated Storage - Jung-Lim Lee; Gregory Yourek (Microorganisms)
Fish is an essential lean protein source worldwide. Unfortunately, fresh fish food products deteriorate rapidly due to microbial spoilage. With consumers’ growing concerns about using chemical preservatives, we propose using natural preservatives as safer alternatives to prevent microbial spoilage. In this study, we used Next-Generation Sequencing (NGS) metagenomics to study microbiomes on catfish fillets at early (day one for all samples), middle (day seven for control store-bought and aquaculture-raised samples, day nine for other treatment store-bought samples, and day eleven for other treatment aquaculture-raised samples), and late (day fifteen for all store-bought, day eleven for control aquaculture-raised samples, and day twenty-seven for other treatment aquaculture-raised samples) points. Store-bought and aquaculture-raised catfish were treated individually with natural preservatives (vinegar, lemon, and grapefruit seed [GSE]). We observed bacterial populations and sequenced 16S NGS libraries of catfish microbes. Vinegar treatment showed the greatest suppression of bacterial growth in both groups, and GSE and lemon treatment had similar levels of suppression in the mid and late points (−4 to −5 Log CFU/g vinegar and −0.1 to −4 Log CFU/g other treatments in aquaculture and −1 to −2 Log CFU/g vinegar and −0.2 to −0.5 Log CFU/g other treatments in store-bought). Aquaculture-raised vinegar treatment samples had similar proportional taxonomy abundance values through storage duration. Pseudomonas, Janthinobacterium, and Camobacteriaceae were the dominant bacteria species in the early point for store-bought fish. Still, Pseudomonas was suppressed by vinegar treatment in the middle point, which allowed for less biased relative abundance compared to other treatments. Chryseobacterium, CK-1C4-19, and Cetobacterium were the dominant bacteria species for early point treatments in aquaculture-raised fish. Still, they remained the predominant bacteria for only aquaculture-raised vinegar samples in the middle and late points, which allowed for a similar relative abundance to fresh catfish. Meanwhile, Pseudomonas in most lemon and GSE samples became the dominant species at a later point. This study provides a better understanding of bacterial spoilage of catfish during storage. Additionally, we showed that natural preservative treatments can effectively extend the shelf-life of fishery products.